Relationship between Antithrombin III Activity and Mortality in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease. Issue 1 (31st December 2022) - Zhang, Shuling; Li, Xiaoguang; Ma, Haili; Zhu, Mengpei; Zhou, Yuequan; Zhang, Qianqian; Peng, Hongxing
Abstract: We aimed to explore the role of antithrombin III (AT-III) activity in diagnosing patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and chronic bronchitis, and its relationship with all-cause mortality of AECOPD patients. We performed univariate and multivariate Cox regression analyses of the factors determining all-cause mortality. We recruited 279 patients with AECOPD and 91 with chronic bronchitis. On admission, patients with AECOPD had lower AT-III activity (80.7 vs. 86.35%, p  = 0.002) and higher neutrophil percentages (70.12 vs. 66.40%, p  = 0.02) than those with chronic bronchitis. The patients who died were older (78 vs. 73 years, p  < 0.001); had higher CRP (39.05 vs. 5.65 mg/L, p  < 0.001), D-dimer (1.72 vs. 0.46 mg/L, p  < 0.001), FIB (3.56 vs. 3.05 g/L, p  = 0.01) levels; and exhibited lower AT-III activity (71.29 vs. 82.94%, p  < 0.001) than the survivors. The AT-III area under the receiver operating characteristic curve for predicting COPD all-cause mortality was 0.75 ( p  < 0.001), optimal cutoff point 79.75%, sensitivity 86.8%, and specificity 57.1%. Multivariate Cox regression analyses showed that increased levels of CRP (HR = 1.005, p  = 0.02), D-dimer (HR = 1.17, p  = 0.01), WBC count (HR = 1.11, p  = 0.002), and reduced AT-III activity (HR = 0.97, p  = 0.02) were independent prognostic factors for all-cause mortality. Patients with AT-III ≤ 79.75% were 4.52 times ( p  = 0.001) more likely to die than those with AT-III > 79.75%. AT-III activity was lower in patients with AECOPD than in those with chronic bronchitis and is potentially useful as an independent predictor of all-cause mortality in patients with AECOPD: reduced AT-III activity and increased CRP and D-dimer levels indicate a higher risk of all-cause mortality.